Assessment of cognitive load using multimedia learning and resting states with deep learning perspective - Qayyum, A. (Institute of Electrical and Electronics Engineers Inc., 2019)
Classification of resting and cognitive states has its importance in brain neuroscience for understating the underlying behaviors of cognition. The human brain is considered as a complex system having different mental states such as resting, active or cognitive states. It is a well-understood fact that the brain activity increases with the increased demand of cognition. The deep learning algorithm based on Pre-trained convolutional neural network (CNN) networks have been used as a transfer learning for the classification of rest and cognitive states and also assessed the cognitive load using brain waves particularly alpha wave. EEG data were collected from 34 human participants at resting and during a learning state. The important EEG electrodes were selected based on the effective connectivity method and after preprocessing, EEG data has been segmented into equal number of segments using selected electrodes to investigate the deep temporal information for cognitive load assessment. The brain waves were extracted using discrete wavelet transform (DWT) for each segment and fed these segments to proposed model for classification and assessment of cognitive load. The results shows that alpha brain wave produced consistent behavior using for all cognition tasks based on pre-trained CNN models for classification and cognitive load assessment. Â© 2018 IEEE